Educação ambiental como estratégia de desenvolvimento local: um estudo de caso - Costa, Andréa Paula de Carestiato (2000)
Study the contribution of Environmental Education projects with a strategic vision of Local Development, understood as a dynamic process of transformation, towards the building of endogenous power so that a particular community is capable of managing itself, developing its socioeconomic potential, maintaining its environmental assets, overcoming its limitations and ensuring a continuous imp[rovement of the quality of life its individuals. The theoretical grounds of this propostiion are based on the concepts of Sustainable Development, Agenda 21, Environmental Education and the water as the generative topic, considering the trends and premises of the National Policy of Hydric Resources. The approach of this topic is based on a Case Study - the Water Course Program. The Water Course Program was oriented to act in the cpontext of the hydrographical basin of the Paraiba do Sul river, with the implementation of a methodology of promoting and supporting the administration of hydric resources in the participating districts, reaching four levels of beneficiaries: institutional, teachers, sutdents and communities. The concept of Local Development was determined as a guide to evaluate the Program and it was applied as reference for this thesis. To evaluate the Case Study, indicators for the Program performance were identified and defined based on the parameters of sustainability and participation of its beneficiaries. The evaluation of the Case Study also included the analysis of indirect impact and weaknesses of the Progam. Based on the adopted methology, the results indicated that the Water Course Program was capable of contirbuting to the Local Development from its strategic conception, considering the range of areas of study that included the districts of Caçapava(SP), Piraí(RJ), Cataguases(MG) and Muriaé(MG).